Pengaruh Aktivitas Fisik Dan Kualitas Tidur Terhadap Prestasi Akademik Peserta Didik Fakultas Kedokteran UKRIDA Angkatan 2019 - maria caecaelia botoor; Rina Priastini Susilowati; Jodie Josephine (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Background: Sleep is an active behavior that is carried out by humans continuously where the quality of sleep is a benchmark for a person to be able to enjoy sleep and maintain the stability of his body. Physical activity that is carried out consistently and regularly can have a great influence on a person's physical condition. Academic achievement is the result of a student's learning which is the most important part of education. This study used a quantitative descriptive study method, cross-sectional by taking data through a questionnaire. The study showed that the Class of 2019 students had good sleep quality and did sufficient physical activity. Where physical activity has a significant effect on the level of academic achievement of the students of the Faculty of Medicine Ukrida Batch 2019. Based on a partial test with a significance value of 0.406 (> 0.05) which shows that there is an influence between physical activity on academic achievement. . Based the partial test with a significance value of 0.220 (> 0.05) which indicates the influence of sleep quality on academic achievement. The F test is a joint test of the regression coefficients by comparing the p-value with a certain level of significance.